Global sourcebook on information technology: Information technology; global scenario, rules and regulations (Vol.1) - Edited by Gandhi, Ved Prakash; Menon, Mridula (Ed.) (New Delhi Kanishka Pub., 2002)
This source book, besides presenting the readers with a perspective on global scenario with respect to information technology, also provides both international and national rules and regulations pertaining to the said subjects.
Keywords: Information Technology; IT rules and regulations